Pelatihan Aplikasi Game Edukasi Kahoot Untuk Meningkatkan Motivasi Belajar Siswa Di Era Pandemi Covid 19 - Diah Aryani; Shine Pintor Siolemba Patiro; Syahrizal Dwi Putra (Terang, 2021)
Community Service Activities carried out at the Integrated Islamic Elementary School (SDIT) Insan Rabbani in the Bekasi area, aimed at providing training in the learning method of the Kahoot educational game method which can be used as an alternative online learning media by taking advantage of opportunities to play games that can support the improvement of educational services. to teachers and students so that they can motivate teaching and learning activities and can support educational services at SDIT Insan Rabbani to be more fun and be able to evaluate the results of learning activities through giving assignments or quizzes and displaying answers to grades for each student and ranking the best three in each assignments or quizzes given so that with the Kahoot application learning objectives are achieved for each subject, especially during the current covid 19 pandemic. In this training, the method used is the online training method using the zoom application by providing exposure related to the Kahoot application and direct practice on the Kahoot application. So that it is hoped that through this training, it is hoped that the ability to achieve an even understanding and mastery of the teacher council supports learning using the Kahoot application as an alternative learning method to create a more interesting, fun and effective learning process. Keywords: educational game, kahoot application, online, zoom application